(5a -3b)(2a +4b)
Multiply each of the terms in the first bracket by the second bracket.
(5a -3b)(2a +4b)
= (5a)*(2a +4b) + (-3b)*(2a +4b)
= 10a^2 + 20ab - 6ab - 12b^2
= 10a^2 +14ab - 12b^2
Don't factor out anything here (such as 2, even though it would be correct and 'prettier'). The point was to expand the 2 brackets.
2007-05-18 07:40:59
·
answer #1
·
answered by Anonymous
·
2⤊
0⤋
You have (5a -3b)(2a +4b).
Now, if you expand out, you get:
5a*2a+5a*4b-3b*2a-3b*4b,
which is:
10a^2+20ab-6ab-12b^2
Simplify, you get
(5a -3b)(2a +4b) = 10a^2+14ab-12b^2
2007-05-18 07:40:23
·
answer #2
·
answered by Mox 2
·
2⤊
0⤋
REMOVE THE BRACKETS
5a*2a + 5a*4b - 3b*2a - 3b * 4b= 10a2+20ab-6ab-12b2
=10a2+14ab-12b2
2007-05-18 07:50:52
·
answer #3
·
answered by preetha_jayakrishnan 1
·
2⤊
0⤋
= 10a² + 20ab - 6ab - 12b²
= 10a² + 14ab - 12b²
= 2.(5a² + 7ab - 6b²)
2007-05-18 08:13:10
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
=10a^2+20ab-6ab-12b^2
=10a^2+14ab-12b^2
2007-05-18 07:45:45
·
answer #5
·
answered by shipdada 3
·
2⤊
0⤋
its 2ab and 6 ab
2007-05-18 07:49:26
·
answer #6
·
answered by melikey2009 2
·
0⤊
2⤋
use FOIL.... and watch your sign, then you shuld be fine.... =)
2007-05-18 07:42:11
·
answer #7
·
answered by L!LO 4
·
2⤊
0⤋